The Role of Clinical Pharmacist in Reducing Drug Related Problems in Decompensated Liver cirrhosis patients - Alobeidi, Ameer; Mohammed Y. Jamal (Iraqi Journal of Pharmaceutical Sciences, 2023)
Patients with decompensated cirrhosis have typically prescribed a combination of therapeutic and prophylactic medications. Polypharmacy increases the probability of medication errors and drug related problems. Clinical pharmacists are highly effective at identifying, resolving, and preventing clinically important drug-related problems in their patients' care. The objectives of the study were the identification and classification of drug-related problems, as well as the discussion of these problems with health care providers (physicians, pharmacists, and nurses) and patients. Reduce their incidence as effectively as possible and educate all research participants on the significance of following their prescribed drug regimen. Prospective, interventional, clinical study for 80 hospitalized decompensated liver cirrhosis patients was designed in two phases, an observational phase to identify drug related problems and classify them according to the Pharmaceutical Care Network Europe classification version 9.1, and an interventional phase to increase the awareness of patients and the health care providers about those problems and to propose a proper solution for each one. The majority of drug-related problems were attributable to the Effect of drug treatment not optimal in 41.5%, Adverse drug events (possibly) occurring in 41.5 %, and Untreated symptoms or indications in 17%. Causes were Drug dose too high in 30.2%, Patient unintentionally using the drug in the wrong way in 22.6%, and Prescribed drug not available in 13.2%. Omeprazole and lactulose were the most common medications causing problems. Acceptance and full implementation were high and observed in 71.7% of pharmacist interventions while 15.1% of the intervention have no agreement. Significant numbers of Iraqi patients with decompensated liver cirrhosis have drug-related problems, and the use of proton pump inhibitors in too high dose was accountable for a large number of problems. Physicians and clinical pharmacists collaborated exceptionally well